Opinions of high school nursing students on integrating medical IT applications in vocational classes in Sisak-Moslavina County - Lučan, Jelena (Array, 2019)
Aim. To examine whether high school nursing students have a positive opinion on using medical IT applications in classes of vocational subjects Nurse in Primary Healthcare and Principles of Administration and whether students’ opinions regarding integrating medical IT applications in classes were related to their knowledge on nursing documentation and attitudes towards its use in primary healthcare. Methods. The study was conducted in the form of a cross-sectional study. In total, there were 84 participants, all students of the Viktorovac High School in Sisak, who filled in a questionnaire consisting of 37 questions. The answers were defined by the Likert rating scale. Results. Sixty-six (79%) students completely agree with the claim that using the application prior to the workplace is useful. 59 (70%) completely agree that being well-trained in using the application ensures a higher quality documenting skills. 40 (48%) students ranked their knowhow in test application as very good (knowhow sufficient for serious work with the application in primary healthcare), and 21 (25%) as excellent. Those students who ranked their knowhow as higher significantly less agree with the claim that there is no need to document nurses’ work and activities. Conclusion. High school nursing students hold positive opinions towards integrating medical IT applications in vocational subjects’ classes. Students’ opinions towards integrating medical IT applications in classes are related to their knowledge on nursing documentation and attitudes towards its use in primary healthcare.